Posterior hip dislocation fracture. Case Presentation - Yaniel Truffin Rodríguez; Osmany Pérez Martínez (Medisur)
The treatment of acetabular fractures is an area of traumatology which is in continuous improvement. The quality of acetabular reduction is the most important factor in the patients´ long-term. Generally, this condition occurs due to high-energy trauma and its associated injuries are frequent. A case of a 29-year-old male patient, is presented with previous healthy history, attended at the Cienfuegos Hospital after suffering a traffic accident and presenting an intra-articular fracture of the distal third of the right radius and a fracture of the posterior right hip dislocation. Due to the surgical procedure complexity, it was decided to present the case, which was operated and followed for more than eight weeks. At the time of the report, the patient is under full weight and continues in the rehabilitation phase.